My hero academia smash!! 2 - Neda, Hirofumi; Cook, Caleb D.; Horikoshi, Kōhei, 1986-; Neda, Hirofumi (San Francisco, CA : VIZ Media, LLC, 2019)
"Izuku Midoriya, a formerly Quirkless boy and now the inheritor of the world's greatest superpower, attends U.A. High, where would-be heroes receive . . . well, some kind of education! From sports festival debacles to choosing questionable hero names and even starting dubious internships, school is all play and no work--until everyone's favorite ninja turtle . . . er, evil villain, Stain, bursts onto the scene!"--Provided by publisher.
Young Adult
English.
Keywords: Ability -- Comic books, strips, etc. -- Fiction; Fantasy comic books, strips, etc; High schools -- Comic books, strips, etc. -- Fiction; Humorous stories; Superheroes -- Comic books, strips, etc. -- Fiction; Supervillains -- Comic books, strips, etc. -- Fiction; Ability -- Comic books, strips, etc. -- Fiction; Fantasy graphic novels; High schools -- Comic books, strips, etc. -- Fiction; Humorous graphic novels; Manga; Superhero graphic novels; Supervillains -- Comic books, strips, etc. -- Fiction; Fantasy comics; Graphic novels; Humorous comics; Superhero comics